A Switched Control Strategy of Heterogeneous Vehicle Platoon for Multiple Objectives With State Constraints - Zhai, Chunjie; Liu, Yonggui; Luo, Fei (IEEE transactions on intelligent transportation systems, 2019)
Vehicle safety, passenger comfort, formation control, and fuel economy are the major objectives in the cooperative adaptive cruise control of intelligent vehicles. However, almost none of the current literature takes all of the above objectives into comprehensive consideration. In this paper, a switched control strategy of heterogeneous vehicle platoon for multiple objectives with state constraints is proposed, in which the above four major objectives are all taken into account. To achieve the four major objectives, the distributed model predictive control with multiple objectives (DMPCMO) is proposed. To solve the problem that the DMPCMO controller cannot be achieved because of the inappropriate initial states of the vehicle platoon or the large perturbations in front of the platoon, the safety controller acting as the emergency brake to guarantee vehicle safety is also designed. The switch between the DMPCMO controller and the safety controller forms the switched control strategy of heterogeneous vehicle platoon for multiple objectives (SCSHPM). Since the DMPCMO controller has to be obtained by solving the nonlinear DMPCMO problem, in order to reduce the computational burden as much as possible, the DMPCMO problem is transformed into non-negative and non-positive 0-1 mixed integer linear programming problems after the fuel consumption table is constructed and calculated off-line. Finally, extensive experiments of heterogeneous platoon under different communication topologies are performed in simulation to demonstrate the effectiveness of the proposed SCSHPM.